Framework for Knowledge Discovery in Educational Video Repositories - Gomes Jr., Jorão; Dias, Laura Lima; Soares, Eduardo Rocha; Barrere, Eduardo; de Souza, Jairo Francisco (Computing and Informatics, 2020)
The ease of creating digital content coupled with technological advancements allows institutions and organizations to further embrace distance learning. Teaching materials also receive attention, because it is difficult for the student to obtain adequate didactic material, being necessary a high effort and knowledge about the material and the repository. This work presents a framework that enables the automatic metadata generation for materials available in educational video repositories. Each module of the framework works autonomously and can be used in isolation, complemented by another technique or replaced by a more appropriate approach to the field of use, such as repositories with other types of media or other content.